Congenital Myasthenic Syndrome Due to Choline Acetyltransferase Mutations in Infants: Clinical Suspicion and Comprehensive Electrophysiological Assessment Are Important for Early Diagnosis. (March 2014) - Dilena, Robertino; Abicht, Angela; Sergi, Paola; Comi, Giacomo P.; Fonzo, Alessio Di; Chidini, Giovanna; Natacci, Federica; Barbieri, Sergio; Lochmüller, Hanns
Congenital myasthenic syndromes are inherited disorders caused by various defects in neuromuscular transmission. Although the typical presentation is fatigable weakness with prominent cranial involvement, neonates can lack these hallmark manifestations, and in those with choline acetyltransferase gene mutations, basal electrophysiological testing can yield negative findings. The authors report the case of a male infant presenting at birth with oculomotor and bulbofacial weakness, hypotonia, clubfoot, and severe respiratory insufficiency. Electromyography showed myogenic signs, and basal repetitive nerve stimulation yielded negative findings. Since age 6 months, the infant had progressively improved, acquiring autonomous respiration. Prolonged subtetanic repetitive nerve stimulation disclosed a marked decremental response compatible with suspected congenital myasthenic syndrome with episodic apnea. Genetic testing identified 2 novel choline acetyltransferase mutations (R470X, F580C). Keeping a high clinical suspicion of this rare condition and undertaking early comprehensive electrophysiological assessments including prolonged repetitive nerve stimulation (10 Hz for 5 minutes) can expedite the diagnosis.